2020
DOI: 10.1016/j.cemconcomp.2019.103498
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-reinforced geopolymer composites: A review

Abstract: There is a burgeoning interest in the development of geopolymers as sustainable construction materials and incombustible inorganic polymers. However, geopolymers show high quasi-brittle behavior. To overcome such weakness, hundreds of research have been focused on development, characterization, and implementation of fiber reinforced geopolymers for a wide range of applications. This paper discusses the rapidly developing state-of-the-art of fiber-reinforced geopolymer composites, focusing on material and geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
263
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 441 publications
(280 citation statements)
references
References 213 publications
(304 reference statements)
13
263
2
2
Order By: Relevance
“…It was found that the microbial retting process is more effective in obtaining fibres with a good appearance, good strength with significant chemical composition with high in cellulose and low in lignin and ash. Due to its higher cellulose content, fibre exhibits better mechanical properties than other natural fibres [ 91 ].…”
Section: Fibres Used In Fcmentioning
confidence: 99%
See 3 more Smart Citations
“…It was found that the microbial retting process is more effective in obtaining fibres with a good appearance, good strength with significant chemical composition with high in cellulose and low in lignin and ash. Due to its higher cellulose content, fibre exhibits better mechanical properties than other natural fibres [ 91 ].…”
Section: Fibres Used In Fcmentioning
confidence: 99%
“…Moreover, palm fibres are among the weakest for use in composites. Tensile strength is 21–60 MPa, and the elastic modulus is 0.6 GPa, which is ten times worse than other natural fibres [ 91 , 97 ]. Data on ultimate stretching are not found in the open literature.…”
Section: Fibres Used In Fcmentioning
confidence: 99%
See 2 more Smart Citations
“…Another technique consists of bonding aramid fiber sheets that age easily. However, structures thus obtained have insufficient strength, and the process of grouting in the back produces a hole [6][7][8][9]. Therefore, there is an urgent need to replace the materials used in strengthening techniques; specifically, materials having good durability and high strength are required.…”
Section: Introductionmentioning
confidence: 99%